2021
DOI: 10.1007/s10989-021-10310-z
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of Fluorine-18 Labelled Peptides for Binding to Cholecystokinin-2 Receptors with High Affinity

Abstract: Many cancers of neuroendocrine origin overexpress cholecystokinin-2 receptors (CCK-2R) including medullary thyroid cancer, small cell lung cancer and other lung carcinoids. Fluorine-18 labelled peptides targeting CCK-2R enable direct visualization and quantification of this receptor in vivo using positron emission tomography imaging. CP04 1 and MG11 2 are two previously described truncated peptides derived from the native CCK-2R hormone ligand, gastrin. The N-terminus of the MG11 2 octopeptide was chemically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In 2021, Khan et al reported the first attempts to introduce scaffolds into the peptide structure of the CCK-2R-targeting minigastrin analog MG11 (glu-Ala-Tyr-Gly-Trp-Met-Asp-Phe-NH 2 ) that enables direct radiofluorination via a nucleophilic aromatic substitution of a nitro group by [ 18 F]fluoride (K 2 CO 3 , kryptofix 2.2.2, azeotropic drying). However, rapid de-fluorination due to the poor chemical stability of these compounds was observed, which illustrates the need for optimized alternatives [ 14 ]. In addition, the earlier studies of Good et al demonstrated a poor metabolic stability for MG11 in vivo [ 15 , 16 ], aggravating the use of this basic structure as a scaffold for radiopharmaceuticals, which is why alternative strategies are desired.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Khan et al reported the first attempts to introduce scaffolds into the peptide structure of the CCK-2R-targeting minigastrin analog MG11 (glu-Ala-Tyr-Gly-Trp-Met-Asp-Phe-NH 2 ) that enables direct radiofluorination via a nucleophilic aromatic substitution of a nitro group by [ 18 F]fluoride (K 2 CO 3 , kryptofix 2.2.2, azeotropic drying). However, rapid de-fluorination due to the poor chemical stability of these compounds was observed, which illustrates the need for optimized alternatives [ 14 ]. In addition, the earlier studies of Good et al demonstrated a poor metabolic stability for MG11 in vivo [ 15 , 16 ], aggravating the use of this basic structure as a scaffold for radiopharmaceuticals, which is why alternative strategies are desired.…”
Section: Introductionmentioning
confidence: 99%